2006
DOI: 10.1207/s15327752jpa8702_03
|View full text |Cite
|
Sign up to set email alerts
|

The MMPI–2 Restructured Clinical Scales: A Paradigmatic Shift in Scale Development

Abstract: Tellegen et al. (2003) proposed fundamental changes in MMPI-2 (Butcher, Dahlstrom, Graham, Tellegen, & Kaemmer, 1989) scale development by discarding empirical scale development in favor of construct validation via Jackson's (1970) sequential system of scale development. As a result of their efforts, a general distress factor (Demoralization) was identified and 8 Restructured Clinical (RC) Scales were developed. Using 7,330 clinical cases from Caldwell's (1997) data set, in this study, we sought to cross-valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…For a more thorough discussion of current recommended uses and cutscores for the FBS see Greiffenstein et al (in press). Rogers, Sewell, Harrison, and Jordan (2006) expressed concerns about the face validity of the Restructured Clinical (RC) Scales and their susceptibility to response style and faking. The RC1 does not appear to have sufficient predictive validity to identify symptom over-reporting in PI litigants or disability claimants under external incentive conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a more thorough discussion of current recommended uses and cutscores for the FBS see Greiffenstein et al (in press). Rogers, Sewell, Harrison, and Jordan (2006) expressed concerns about the face validity of the Restructured Clinical (RC) Scales and their susceptibility to response style and faking. The RC1 does not appear to have sufficient predictive validity to identify symptom over-reporting in PI litigants or disability claimants under external incentive conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this basic research design may suffer from generalizability to real-world settings. A better research design, employment of probable known groups, has direct clinical relevance and generalizability as it relies on a two part approach: (1) establishment of criterion groups (malingerers and bona fide patients), and (2) statistical analysis between the criterion groups (Rogers, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…They were derived using Jackson's (1970) sequential system of scale development and factor-analytic techniques (Rogers, Sewell, Harrison, & Jordan, 2006). Such procedures can be used to create homogeneous subscales with strong divergence and discriminability (for a review see Lanyon & Goodstein, 1997).…”
Section: Mmpi-2 Restructured Formmentioning
confidence: 99%
“…176-177), resulting in a "drastically downsized" (p. 175) set of eight Clinical scales . Recommendations that the RC scales could be used to clarify interpretation of the Clinical scales (Tellegen et al, 2003) were suggested to be premature (Rogers, Sewell, Harrison, & Jordan, 2006). A particularly thorny issue for use of the RC scales in clinical settings was the observation that the RC scales did not have elevations in the clinical range, although the traditional Clinical scales did (Megargee, 2006;Wallace & Liljequist, 2005).…”
mentioning
confidence: 99%